PENGGUNAAN MULTIMEDIA ONLINE DALAM PEMBELAJARAN - A. Marjuni; Hamzah Harun (Idaarah: Jurnal Manajemen Pendidikan, 2019)
The use of technology and information as multimedia learning has a very strategic function. Media is seen as one of the factors that can improve the learning process because the media has strategic roles and functions that can directly or indirectly affect the motivation, interests, and attention of students. The function of multimedia in learning is to overcome the limitations of students’ experiences, be able to transcend classroom boundaries, enable direct interaction between students and their environment, produce uniform observations, instill the basic concepts that are true, concrete, and realistic. Multimedia can arouse new desires and interests and arouse students’ motivation to learn and provide an integral or comprehensive experience from the concrete to the abstract. The advantages of using multimedia in learning include being able to improve students’ ability to understand an abstract concept more easily, in addition to the use of computer media in the form of multimedia can give a positive impression to the teacher because it can help teachers explain the contents of the lesson to students, streamline time, and increase students’ motivation in learning.